2017
DOI: 10.37358/rc.17.6.5639
|View full text |Cite
|
Sign up to set email alerts
|

Study of Phosphocalcic Glasses from SiO2-CaO-P2O5 System with and Without Silver II. The bioactivity analysis by FTIR, SEM methods and microbiological study of silver-doped glasses

Abstract: The study in vitro of the glass powders bioactivity was performed by soaking them in simulated body fluid for 3 to 21 days at a temperature of 37�C and pH = 7.20. The synthesis de novo of hydroxyapatite, post soaking was confirmed by Fourier Transform Infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The study of the antimicrobial activity was performed by microbiological examination on two strains of pathogenic bacteria involved in postoperative nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It can be seen that both bacterial strains grew in extremely high numbers, superinfecting the plates, which shows that they grew optimally, not being stressed by any disturbing factor (metal dopant, culture medium, incubation temperature). This shows that undoped P-glass with metal ions does not show antimicrobial activity on any bacterial strains, which was expected, so it does not show bactericidal or bacteriostatic effect [1][2][3][4][5]. 2.e) in the presence of 0.1 g PA glass powder with 5% silver doped.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…It can be seen that both bacterial strains grew in extremely high numbers, superinfecting the plates, which shows that they grew optimally, not being stressed by any disturbing factor (metal dopant, culture medium, incubation temperature). This shows that undoped P-glass with metal ions does not show antimicrobial activity on any bacterial strains, which was expected, so it does not show bactericidal or bacteriostatic effect [1][2][3][4][5]. 2.e) in the presence of 0.1 g PA glass powder with 5% silver doped.…”
Section: Methodsmentioning
confidence: 76%
“…These were purchased from Mediclim Bucharest, in the form of pure lyophilized cultures: Escherichia coli ATCC reg. 25922 -Gram-negative bacteria, conditionally pathogenic, extremely resistant to antibiotic treatment and, respectively, Staphylococcus aureus ATCC reg 25923 -Gram-positive bacteria, pathogenic, with the highest risk of postoperative infection, in prosthetic surgery and bone reconstruction [1][2][3][4][5]. The aim of doped with silver was to determine a possible bacteriostatic/bactericidal capacity of phosphocalcic bioactive glasses, known as the antimicrobial capacity of silver, while doping with the copper ions was a challenge, starting from the analogy of copper ion activity in different pesticides used in agriculture for some bacterial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The 1160 cm −1 band is the C-O stretching vibration, and the C-C skeleton stretching vibration absorption band of cellulose intramolecular ether, which is the characteristic band of cellulose structure [35]. The band at 1060 cm −1 is the Si-O stretching vibration band of inorganic materials such as SiO 2 [36]. Compared with untreated wheat straw powder, the C-O stretching vibration band and the C-C skeleton stretching vibration absorption at 1160 cm −1 increased after the alkaline hydrogen peroxide, which indicated that the purity of SiO 2 and cellulose was improved because the removal of lignin leaves a large amount of cellulose and SiO 2 after the reaction.…”
Section: Resultsmentioning
confidence: 99%